Optimalisasi Pencegahan Polio Melalui Program Berikan Dua Tetes Manis Imunisasi Polio: Pengabdian - Siti Utami Dewi; Agustina, Ayuda; Hemma Siti Rahayu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Polio is still a health threat in some areas, despite extensive immunization programs. This community service activity was carried out by Fatmawati College of Health Sciences together with Puskesmas Cilandak District with the aim of preventing polio through immunization and education programs. The method of implementation is by providing polio immunization to children, as well as providing education to parents about the importance of vaccination. This activity was carried out in several locations, including Posyandu and schools, with a focus on increasing community awareness. The results of the activities showed an increase in community knowledge and participation in the immunization program, although there were still obstacles such as lack of information and resources. In conclusion, collaboration between the government, educational institutions, and communities is essential to improve polio immunization coverage. Continuous education and training for health workers are also needed to ensure the success of the program. With these measures, it is hoped that the polio immunization program can continue to be effective and have a positive impact on public health, as well as prevent the return of polio disease in the future.